AN ANALYSIS OF CATFISH FARMING BUSINESS OPPORTUNITIES AS A MEANS TO INCREASE COMMUNITY INCOME IN PONDOK BABARIS VILLAGE, SUNGAI PANDAN SUB-DISTRICT, HULU SUNGAI UTARA REGENCY - Ilmi, Khairul; Agustina, Eka Santi (PPPM STIA Amuntai, 2025)
This study aims to analyze the impact of catfish farming on increasing community income in Pondok Babaris Village, Sungai Pandan District, Hulu Sungai Utara Regency. The research applies a quantitative approach, with data collected through observation, questionnaires, interviews, and documentation. The data were analyzed using simple linear regression / descriptive statistics with the help of SPSS version 25. The results indicate that partially, business capital and harvest frequency do not significantly influence income, whereas business profit has a positive and significant effect. Simultaneously, the variables of capital, harvest frequency, and profit significantly affect the community’s income. These findings demonstrate that catfish farming can serve as a viable economic alternative for rural communities to create employment opportunities and improve economic welfare